PENELITIAN PENGHINDARAN PAJAK DI INDONESIA - Nurul Herawati; Rahmawati Rahmawati; Bandi Bandi; Doddy Setiawan (Universitas Trunojoyo Madura, 2019)
This study aims to provide an overview of the development of tax avoidance research in Indonesia from 12 accredited national journals ranking 1 2. The study sample included 27 articles that researched tax avoidance in Indonesia over the 2012 – 2018 observation period. Mapping was done by classifying articles based on research topics (antecedents and consequences), population and research samples, tax avoidance proxies, and citation analysis (Hesford, Lee, Stede, Young, 2007). The mapping results show that the publication of the most tax avoidance research in Jurnal Akuntansi (22%). The antecedents topic dominates tax avoidance research and there are 28 antecedent variables from 23 articles. The most widely studied antecedent variable is corporate governance. The consequence topics are 4 articles with 5 variables. The dominating research sample was manufacturing companies (41%) and 63% of articles used a number of samples above 100. The most widely used tax avoidance proxies were ETR, Current ETR, and ETR Cash. The tax avoidance research citation rate reached 163 in the observation period and 67% of the articles received citations. The most cited topics are antecedents of corporate governance, company size, liquidity, leverage, and earnings management.PENELITIAN PENGHINDARAN PAJAK DI INDONESIA